Are there clinical and subclinical/pathological forms of Paget’s disease of the breast? - Pelorca, Rafael José Fábio; de Oliveira-Junior, Idam; Vieira, René Aloisio da Costa (Frontiers in Oncology, 2023)
Introduction: Breast disease management has changed over recent decades, related to molecular subtype, oncoplastic surgery and targeted therapies. Nevertheless, literature on Paget's disease of the breast (PDB), initially described as a clinical entity and now considered a multifocal/multicentric disease. Methods: PDB was classified as clinical in the presence of areolar abnormalities and as subclinical/pathological in all other cases. Clinical and prognostic data were evaluated and compared between the different presentation forms. Statistics comprised descriptive analysis, inter-group comparison (chi-square and Mann-Whitney tests) and overall and cancer-specific survival rates (Kaplan-Meier method and the log-rank test). Results: Of 85 patients included in this series, PDB was clinical in 58.8%. Overall, 27.1% had stage 0 and 92.9% had multifocal/multicentric disease. Most patients (83.5%) had the HER2 or luminal HER2 molecular subtype. Patients with clinical PDB had a higher rate of in situ disease (p=0.028) and were more likely to undergo breast-conserving surgery (p<0.001). Most of the 43 patients with HER2 invasive disease received anti-HER therapy. Mean follow-up time was 71.2 ± 43.3 months. Cancer-specific actuarial survival at 60 and 120 months was 92.3% and 83.1%, respectively. Survival was unaffected by the clinical form of PDB (p=0.275), anti-HER therapy (p=0.509) or oncoplastic surgery (p=0.821). Conversely, clinical stage affected survival significantly (p≤0.001).PDB is a rare condition associated with multifocality/multicentricity and HER2 overexpression. Cases of clinical disease and those of subclinical/pathological disease differ significantly. Further studies are required to evaluate the clinical/areolar disease and the impact of advances in breast disease management on PDB.